(untitled) (Altre Modernità, 2019)
Reshmi Dutta-Flanders, The Language of Suspense in Crime Fiction. A Linguistic Stylistic Approach (London, Palgrave Macmillan, 2017, 500 pp. ISBN 978-1-137-47027-0) by Esterino Adami